Performance evaluation of inductive coupling probes using electromagnetic simulation - Tan, Lok Yin (Nanyang Technological University, 2020)
Commercially available current probes come in all shapes and sizes due to different targeted engineering applications. For example, a small and compact probe can be used for electronic controller panel measurement while a larger probe can be used for current monitoring in high power systems. In order to effectively study how the physical characteristics of the current probe can affect the performance of the current probe, electromagnetic (EM) simulations can be helpful. EM simulation software, CST Microwave Studio is chosen for the analysis in this report. It uses the Finite Element Method (FEM) to characterise different types of inductive coupling probes in terms of S-parameters which are then are converted to ABCD Parameters for further analysis and for ease of interpretation.